2021
DOI: 10.1021/acsami.1c04874
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne Based Ternary GD-CuI-NiTiO3 S-Scheme Heterjunction Photocatalyst for Hydrogen Evolution

Abstract: As the demand of fossil fuels continues to expand, hydrogen energy is considered a promising alternative energy. In this work, the NiTiO 3 −CuI-GD ternary system was successfully constructed based on morphology modulation and energy band structure design. First, the one-pot method was used to cleverly embed the cubes CuI in the stacked graphdiyne (GD) to prepare the hybrid CuI-GD, and CuI-GD was anchored on the surface of NiTiO 3 by simple physical stirring. The unique spatial arrangement of the composite cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…Compared to LDH-2, the composite catalyst LDH-2@Cu 2 S has the lowest initial potential; this might be due to the fast electron transfer from the LDH-2@Cu 2 S interface to the active species surface to reduce the H 2 O molecules. Thus, the decrease in reaction potential is closely related to the formation of the p–n heterojunction, which accelerated the transfer of photogenerated carriers; , this result confirmed that the LDH-2@Cu 2 S heterojunction has a significant effect on the HER activity. Figure d shows the flat band potential ( E fb ) of LDH-2, which is −0.59 eV.…”
Section: Results and Discussionsupporting
confidence: 62%
“…Compared to LDH-2, the composite catalyst LDH-2@Cu 2 S has the lowest initial potential; this might be due to the fast electron transfer from the LDH-2@Cu 2 S interface to the active species surface to reduce the H 2 O molecules. Thus, the decrease in reaction potential is closely related to the formation of the p–n heterojunction, which accelerated the transfer of photogenerated carriers; , this result confirmed that the LDH-2@Cu 2 S heterojunction has a significant effect on the HER activity. Figure d shows the flat band potential ( E fb ) of LDH-2, which is −0.59 eV.…”
Section: Results and Discussionsupporting
confidence: 62%
“…As shown in Figure g, the polycrystalline bright spots are obvious in the figure. The distribution area is wide, and there are amorphous circles at the same time, indicating that the composite material shows a mixed structure of a high-crystalline state and a low-crystalline state. , The energy-dispersive X-ray (EDX) image of P@Co 3 O 4 can prove the presence of O, Co, and P elements (Figure h). At the same time, the elemental mapping analysis of P@Co 3 O 4 (Figure i) shows that O, Co, and P are dispersed in the polyhedral structure.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, when comparing the hydrogen production performance of GDY–CuBr with other systems reported in the literature of the same type, GDY–CuBr has prominent superior hydrogen evolution activity. 67,68 As shown in Table 2, the comparison results demonstrate that the hydrogen evolution of GDY–CuBr has a higher performance than previously reported literature. This result indicates the great potential of GDY–CuBr in the field of photocatalysis.…”
Section: Resultsmentioning
confidence: 73%